FILSAFAT PRAGMATISME DALAM IMPLEMENTASI KURIKULUM MERDEKA UNTUK MENJAWAB TANTANGAN PENDIDIKAN ABAD 21-BERBASIS LITERATUR REVIEW - Rini Nurbayti; Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
21st-century education demands relevant skills to prepare students to face challenges in the workplace and society. The philosophy of pragmatism, with its emphasis on experiential learning, provides an effective approach to implementing the Independent Curriculum. This study aims to analyze how the principles of pragmatism can strengthen the implementation of the Independent Curriculum in the context of 21st-century education. Through a literature review of 10 accredited articles, it was found that the application of pragmatism supports interactive, collaborative, and project-based learning, as well as relevance to technology. The results indicate that this approach can improve students' critical, creative, and adaptive thinking skills. Therefore, the implementation of the Independent Curriculum, based on the philosophy of pragmatism, is a strategic solution to address the challenges of 21st-century education.